Human Rights, War, Postwar and Memory in El Salvador: About Life and Academic Work of Ralph Sprenkels - Melara Minero, Lidice Michelle (2021)
Dutch born anthropologist and historian Ralph Sprenkels, died unexpectedly in September 2019. Sprenkels devoted most of his research to understanding and explaining the conflict and post-war in El Salvador. This article describes the journey of how Sprenkels became linked to El Salvador and the impact this had on his life. He became a human rights activist, and later, dedicating himself to the investigation of postwar political polarization, to the study of memory and transitional justice, as well as one of the most important revolutionary movements in Latin America: the FMLN. In this sense, the article provides a general account of his work, which concludes that Sprenkel’s academic work constitutes a significant contribution to the understanding of Salvadorian reality, making significant theoretical contributions to new research.